Typification of three Carex nothospecies names dedicated to Czech botanists by J. Podpěra - Řepka, Radomír; Taraška, Vojtěch (Phytotaxa, 2023)
The article elucidates the taxonomic identity of the putative nothospecies Carex ×binderi, C. ×filkukae and C. ×lausii described by Josef Podpěra from the territory of Bohemia and Moravia (Czech Republic) in the early 20th century. Herbarium material obviously handled by J. Podpěra was retrieved and thoroughly compared with that of the presumed parental taxa, but morphological evidence point to a hybrid origin only for C. ×binderi, corresponding to C. ×leutzii. By contrast, plants of C. ×filkukae and C. ×lausii could be assigned to atypical individuals of C. leporina and C. acutiformis, respectively. Lectotypes for all treated names are designated here, which turns J. Podpěra’s names into synonymy of the above-mentioned species and nothospecies names.